Persistence of wastewater antibiotic resistant bacteria and their genes in human fecal material - Scaccia, Nazareno (2020)
Domestic wastewater is a recognized source of antibiotic resistant bacteria and antibiotic resistance genes (ARB&ARGs), whose risk of transmission to humans cannot be ignored. The fitness of wastewater ARB in the complex fecal microbiota of a healthy human was investigated in feces-based microcosm assays (FMAs). FMAs were inoculated with two wastewater isolates, Escherichia coli strain A2FCC14 (MLST ST131) and Enterococcus faecium strain H1EV10 (MLST ST78), harboring the ARGs blaTEM, blaCTX, blaOXA-A and vanA, respectively. The FMAs, incubated in the presence or absence of oxygen or in the presence or absence of the antibiotics cefotaxime or vancomycin, were monitored based on cultivation, ARGs quantification and bacterial community analysis. The fecal bacterial community was dominated by members of the phyla Firmicutes, Bacteroidetes, Actinobacteria, Proteobacteria and Verrucomicrobia. The ARGs harbored by the wastewater isolates could be quantified after one week, in FMAs incubated under both aerobic and anaerobic conditions. These observations were not significantly different in FMAs incubated anaerobically, supplemented with sub-inhibitory concentrations of cefotaxime or vancomycin. The observation that ARGs of wastewater ARB persisted in presence of the human fecal microbiota for at least one week supports the hypothesis of a potential transmission to humans, a topic that deserves further investigation.